The interferon response at the intersection of genome integrity and innate immunity - Duzanic, Filip D.; Penengo, Lorenza (DNA repair, 2025)
In recent years, numerous reports indicated that, besides pathogen infections, DNA replication stress and defective DNA repair can trigger the innate immune response by introducing a state of viral mimicry, due to cytosolic accumulation of the self-nucleic acid species, which culminates in the activation of type I interferon (IFN) pathway. In turn, IFN upregulates a variety of factors mutually implicated in immune- and genome-related mechanisms, shedding light on the unprecedented causality between genome stability and innate immunity. Intriguingly, in addition to being induced by replication stress, IFN-regulated factors can also promote it, pinpointing IFN signaling as both a consequence and a cause of replication stress. Here, we provide an overview of the factors and molecular mechanisms implicated in the evolutionary conserved crosstalk between genome maintenance and innate immunity, highlighting the role of the IFN-stimulated gene 15 (ISG15), which appears to be at the hub of this intersection. Moreover, we discuss the potential significance and clinical implications of the immune-mediated modulation of DNA replication and repair upon pathogen infection and in human diseases such as cancer and autoinflammatory syndromes. Finally, we discuss the relevant open questions and future directions. •Here we summarize recent finding on the evolutionary conserved interplay between genome maintenance and interferon pathway.•Molecular details of this crosstalk are presented, emphasizing the events governing DNA replication fork dynamics.•Interferon Stimulated Gene 15 is a key factor in this crosstalk, being both a cause and a consequence of replication stress.•Potential clinical implications regarding human malignancies, autoinflammatory and neurodegenerative diseases are discussed.